Supply Chain Analysis of Farmed Exotic Carps in Jammu and Kashmir, India - Nisar, Ubair; Kumar, Nalini Ranjan (Fishery Technology, 2018)
The study was conducted in the state of Jammu and Kashmir where the major fish marketing stakeholders like fish farmers, pre-harvesting contractors, wholesalers, retailers and fish vendors were interviewed. In Jammu and Kashmir the culture of exotic carps like grass carp (Ctenopharyngodon idella) (Steindachner, 1866), silver carp (Hypophthalmichthys molitrix) (Valenciennes, 1844) and common carp (Cyprinus carpio) (Linnaeus, 1758) is carried out and the culture has proved to be economical. The disposal pattern of the exotic carp revealed that the overall local consumption of the fish by the farmers in the state was less around 3.79% only as it was a source of livelihood, so farmers preferred to sell rather than consuming themselves. The most significant effect on the marketing costs of the locally cultured exotic fishes was observed by the use of excess casual labours and water charges. There were three major Supply Chains (SC) prevailing in the state (SC I, SC II and SC III) and amongst them the marketing channel III was most efficient (17.82) with highest producers share in consumer’s rupee (94.69) where the farmers were directly selling the production to the consumers. The state was not self-sufficient in meeting the demands of the people so fishes produced in other states were also marketed.